Uganda [in Strategies and priorities for African agriculture] - Benin, Samuel; Thurlow, James; Diao, Xinshen; Kebba, Allen; Ofwono, Nelson (International Food Policy Research Institute, 2012)
Uganda is often heralded as an African success story. The country re-established political stability after the civil wars following Idi Amin’s overthrow and subsequently experienced strong economic growth during the 1990s. Gross domestic product (GDP) grew rapidly at almost 4 percent annually in per capita terms during 1993–2000 (Uganda, BOS 2008a). At least part of this rapid growth was due to a program of economic reforms, although the implications of these reforms were not universally positive (see, for example, Dijkstra and Van Donge 2001). Economic growth during the 1990s was also broadly based, with per capita agricultural GDP rising by about 1.5 percent per year, driven by both food and traditional export crops. Economywide growth greatly reduced poverty in both rural and urban areas (Uganda, BOS 2008b). Moreover, poverty rates fell fast enough to offset high population growth, and by 2000 there were almost three million fewer people living below the poverty line than in 1993. Agricultural growth thus played a key role during Uganda’s successful recovery period by fostering broad-based growth and poverty reduction (Kappel, Lay, and Steiner 2005).